Analisis Kelayakan Usaha Peternakan Ayam Pedaging dengan Pola Kemitraan di Kecamatan Ciampea Kabupaten Bogor - Hasan Subkhie; - Suryahadi; Amiruddin Saleh (Institut Pertanian Bogor, 2012)
Poultry commodities have a good prospect of market, because it is supported by its character that easily accepted by Indonesian people. People of Indonesia that nearly 220 million people and can be growth 1,4 percent per year are potential market of chicken ranch business. The aims of this study are: (a) identify the system of chicken management ranch business by plasma partnership system with PT Charoen Pokphand Indonesia, (b) analyz feasibility of chicken ranch business by plasma partnership system with PT Charoen Pokphand Indonesia, (c) arrange the strategies that should be done by plasma farmer in Ciampea Bogor, which are doing partnerships with PT Charoen Pokphand Indonesia. Data collecting was conducted through direct observation of four plasma chicken ranch business through interview with the owner of plasma chicken ranch. The data consisted of primary and secondary data were used to identify and evaluate system of management of chicken ranch business by plasma partnership system with PT Charoen Pokphand Indonesia. The data were also used to analyze feasibility of chicken ranch business by plasma partnership system with PT Charoen Pokphand Indonesia and to know the good strategies that had to be developed generally in four locations of study through SWOT analysis. The good chicken ranch business should use hencoop with stage system which made by permanent materials with monitoring system roof made by genteng. By doing good practice management on starter, grower and finisher period and also pressing the Feed Conversion Ratio (FCR) value until 1,5, so that the chicken ranch business can give much benefits. Feasibility analysis of financial aspect with population scale 22.000 chickens, 14.000 chickens, 8.000 chickens and 4.000 chickens with interest rate 16%, shows that chicken ranch business is feasible to be implemented and developed if can reach FCR value 1,5. Based on the SWOT analysis, alternative strategies for plasma chicken ranch business development are improving productivity to increase benefits, increasing efficiency of using production factors, being proactive to solve the techniques problem, increasing the knowledge of handling disease problem, being optimal in using production factors, increasing practice management according to standard and increasing farmer’s knowledge about the good practice management.